A Consumer Satisfaction Survey of Civilly Committed Sex Offenders in Illinois. (April 2014) - Levenson, Jill S.; Prescott, David S.; Jumper, Shan
The purpose of this study was to obtain feedback from civilly committed sex offenders ( N = 113) about the components of treatment that they believed to be most important and helpful in preventing reoffense. Participants were also asked to rate their satisfaction with the treatment process and therapists. Victim empathy and accountability were rated as the most important elements of treatment, along with skills for preventing relapse and methods for controlling sexual arousal. There was a fairly robust correlation between client perceptions of importance and satisfaction on most treatment components. Some clients expressed concerns about respect, confidentiality, and judgmental attitudes of some therapists. Because civilly committed sex offenders are considered to be among the most likely to reoffend, strategies are discussed for engagement of this population in a meaningful process of change.